Harnessing Knowledge Management for SME Sustainability and Competitiveness: A Dynamic Capabilities Conceptual Framework - Mochamad Purnomo; Shah Iskandar Fahmie; Ratih Pratiwi; Mohamad Hazeem Sidik; Nur Fadiah Mohd Zawawi; Nurul Muna Mohamad; Syafiq Aryanta Manggala Saputra (AKSES: Jurnal Ekonomi dan Bisnis, 2026)
This article presents a conceptual framework for Knowledge Management Excellence in SME Sustainability. The key factors influencing the sustainability of SME were identified from previous literature and empirical studies. The framework was built on established sustainability and capability models, emphasising the strategic role of knowledge management in driving long-term competitiveness. The proposed framework positions dynamic capabilities as a foundation for developing a knowledge management excellence model, specifically sensing, seizing, and transforming/reconfiguring, enabling SME to adapt to environmental changes, exploit opportunities, and maintain sustainable performance. Within this framework, information sharing, learning culture, and technological readiness serve as critical enablers that enhance knowledge utilisation and innovation capacity. By integrating these elements, SME can strengthen their adaptability and resilience in an increasingly volatile business environment. The study reorganises and extends existing sustainability factors into new sub-categories, providing deeper insights into how knowledge management can reinforce sustainability and competitiveness. Ultimately, the proposed framework provides a structured conceptual foundation to guide both academic research and managerial practice in fostering sustainable growth among SME